The Effect of The Use of Practicum Modules on Students' Understanding of Using The MYOB Application in The Department of Economic Education of Gorontalo State University - Mohamad, Puja; Mahmud, Melizubaida; Dama, Maya Novrita; Hafid, Radia; Damiti, Fatmawaty (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this study is to find out whether there is an influence of the use of practicum modules on the understanding of students of the Department of Economics Education, Faculty of Economics and Business, Gorontalo State University in using the MYOB application. This study uses a descriptive quantitative approach with a sample of 58 people. The instruments used are questionnaires and test questions. The data analysis technique used is simple linear regression analysis. Based on the results of data analysis, it was found that there was a significant influence of the use of the practicum module on the understanding of students of the Department of Economics Education, Faculty of Economics and Business, Gorontalo State University in using the MYOB application. The influence of the practicum module on the understanding of students of the Department of Economics Education, Faculty of Economics and Business, Gorontalo State University in using the MYOB application is 37.5% and the remaining 62.5% is influenced by other variables that are not examined in this study.